The Shift in U.S. Strategic Ambiguity toward Taiwan: A Foreign Policy Change Approach from Trump to Biden - Larasati, Ria Agustina; Larasati (Institute of Social and Political Science Jakarta (Institut Ilmu Sosial dan Ilmu Politik Jakarta - IISIP Jakarta), 2025)
This article examines the shift of U.S. foreign policy toward Taiwan (2017–2024) amid intensifying strategic competition with China. Addressing a key research gap, it systematically links the U.S. strategy of strategic ambiguity with internal and external dynamics across two administrations that adopted differing approaches to Taiwan. Using the qualitative descriptive method and the Foreign Policy Change framework, the study analyzes three main drivers of policy adjustment: international political shifts, global economic interdependence, and domestic pressures. The findings show that although strategic ambiguity is officially retained, U.S. policy has shifted toward a more managed form of strategic clarity. This transition is shaped by contrasting leadership styles: Trump’s symbolic and transactional posture versus Biden’s more structured approach embedded in a rules-based international order. These changes have heightened tensions in U.S.–China strategic relations. Overall, the article contributes to the foreign policy theory by explaining how major powers recalibrate policy amid evolving global rivalry.